Aberrantly activated Wnt/β‐catenin pathway co‐receptors LRP5 and LRP6 regulate osteoblast differentiation in the developing coronal sutures of an Apert syndrome (Fgfr2S252W/+) mouse model. Issue 3 (9th September 2020) - Min Swe, Nay Myo; Kobayashi, Yukiho; Kamimoto, Hiroyuki; Moriyama, Keiji
Abstract: Background: Apert syndrome is an autosomal, dominant inherited disorder characterized by craniosynostosis and syndactyly caused by gain‐of‐function mutations in the fibroblast growth factor receptor 2 ( FGFR2 ) gene. Wnt/β‐catenin signaling plays critical roles in regulating the skeletal development. Here, we analyzed the role of this pathway in the developing coronal sutures (CS) of a murine Apert syndrome model ( Fgfr2 S252W/+ ). Results: We observed aberrantly increased mRNA expression of Lrp5 and Lrp6 in CS of Fgfr2 S252W/+ mice, whereas both wild type (WT) and Fgfr2 S252W/+ mice showed similar expression of other Wnt/β‐catenin‐related genes, such as Wnt3, Wnt3a, Fzd4, Fzd6, Axin2, and Dkk1 as evidenced by in situ hybridization. Significantly increased Lrp5 and Lrp6 mRNA expression was observed by quantitative PCR analysis of cultured cells isolated from CS of Fgfr2 S252W/+ mice. Phospho‐LRP5, phospho‐LRP6, and non‐phospho‐β‐catenin were upregulated in Fgfr2 S252W/+ CS compared with that in WT CS. Short‐interfering RNA targeting Lrp5 and Lrp6 significantly reduced runt‐related transcription factor 2, collagen type 1 alpha 1, and osteocalcin mRNA expression, and alkaline phosphatase activity in cultured cells. Conclusions: The Wnt/β‐catenin pathway was activated in the CS of Fgfr2 S252W/+ mice during craniofacial development, suggesting the involvement of the Wnt/β‐catenin pathway in the pathogenesis of CS synostosis in Fgfr2 S252W/+ mice. Key Findings: Analysis of expression patterns of Wnt pathway‐related genes revealed enhanced expression of Lrp5 and Lrp6 in CS of Fgfr2 S252W/+ mice Increased expression of phosphorylated Wnt pathway co‐receptors LRP5 and LRP6 in Fgfr2 S252W/+ CS Fgfr2 S252W/+ mice showed upregulation of Wnt/β‐catenin signaling in the CS. Primary cultured cells derived from CS of Fgfr2 S252W/+ mice exhibited higher expression of Lrp5 and Lrp6. LRP5 and LPR6 showed osteogenic effects on CS‐derived primary cultured cells.